Strategic Human Resource Management and Employment Relations An International Perspective (Springer Texts in Business and Economics,, 2018)
This book analyses a collection of key strategic human resource management (HRM) and employment relations (ER) topics. The book follows a unique pedagogical design employing problem-based learning and participant-centred learning approaches, both of which the author has extensive experience in implementing with post-graduate learners. The book also prepares the learner to use these approaches, and has resources for the instructor. The first part of the book provides a very focussed research commentary highlighting the key theoretical approaches in HRM and ER. The second part offers details of the design and implementation of strategic HRM and ER practices. The third part features a selection of contemporary research-based case studies that bring to life the debates and tensions inherent in the field of strategic HRM and ER.